The Lycopodiaceae of Guyana, Suriname, and French Guiana - Øllgaard, Benjamin; Boudrie, Michel; Cremers, Georges (Phytotaxa, 2020)
The present paper provides keys to the genera and species of Lycopodiaceae for the 5 genera and 25 species recorded from Guyana, Suriname, and French Guiana. The treatment includes nomenclature, descriptions of species, and information about distribution and habitats, and notes on problems of species delimitation and infraspecific variation. All species are illustrated, and representative specimens are cited.